OBJECTIVE FACTORS CAUSING PODODERMATITIS IN BREEDED CATTLE (Conferencea, 2022)
In this article, several objective causes of pododermatitis in cattle of different breeds brought to our country from abroad are discussed, in addition, the causes of finger and hoof diseases are some deficiencies in the feed ration, the importance of the base in keeping cattle, an important role in the prevention of pododermatitis is listed.